Estratégias empresariais do setor de energia eólica no Brasil diante dos desafios das mudanças climáticas - Siebra, Alexandra Alencar (2012)
The productive operation of companies causes environmental degradation, worsened by the increasing energy demand and global dependency of non-renewable resources. One of the most serious impacts involves climate change due to emissions of greenhouse gases, which affect all the companies, including the wind sector, directly or indirectly. Companies strategically respond differently depending on how they are affected and the market they serve. This work analyzes the influence of stakeholders and political, technological and environmental factors in the strategies of brazilian wind energy producers and their suppliers, as well as the key practices used by these companies in response to challenges posed by climate change. Methodologically, it was opted to carry out bibliographic, documental and field search. In the field research was conducted an exploratory study, qualitative, with the application of interviews aimed to identify the determining factors that influence the strategies of wind power sector in the state of Ceará. Then was applied a quantitative questionnaire to brazilian wind energy producers and their suppliers. The results suggest that the factors of most influence in the business strategies of brazilian wind energy producers and their suppliers are the politicians, with emphasis on energy auctions promoted by ANEEL, through which are achieved most competitive prices in energy market. The most influential stakeholder is the shareholder, and this influence indicates the coercive power of the shareholders in the strategic decisions of brazilian wind energy producers and their suppliers. The results indicate that the business practice more widely adopted was the innovation, and the result showed that in the pursuit for mitigating the effects of climate change the companies are likely to stimulate the development of cleaner and sustainable processes, and reduce costs related to their processes, and therefore obtain competitive advantage. The adoption of business practices in order to mitigate or compensate the effects of climate change depends on the influence of external factors. The pressure and influence of stakeholders have great importance for the sector of renewable energies like wind power be consolidated in the world energy planning. In the last decade, brazilian wind power projects received more tax incentives and technology investments. In the context, the state of Ceará aims with their actions to increase their competitiveness in this segment and offer a viable alternative to minimize the environmental impacts of climate change.